Vertical integration by oil exporting countries - Horst Siebert; Michael Rauscher (Intereconomics, 1985)
Most oil-producing countries have now nationalised their oil reserves and are pursuing their own pricing and marketing policies; in recent years some of them have attempted to extend their influence over the oil market by undertaking processing activities downstream from oil production. What motives underlie this strategy of vertical integration? What is its economic justification? What effects will it have on oil-importing countries?
Keywords: 330; Mineralölverarbeitung; OPEC-Staaten